2012
DOI: 10.4067/s0718-34292012000300011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la tolerancia a estrés por sequía en cuatro genotipos naturalizados de vid (Vitis vinifera) provenientes del norte de Chile

Abstract: Evaluación de la tolerancia a estrés por sequía en cuatro genotipos naturalizados de vid (Vitis vinifera) provenientes del norte de Chile RESUMENEl cultivo de la vid (Vitis vinifera) se caracteriza por sufrir sequías estacionales en la mayoría de las regiones productoras, situación que se incrementa en ambientes áridos y semiáridos de Chile, los cuales han sufrido disminuciones de precipitaciones y prolongados periodos de sequía, siendo una de las principales problemáticas que afectan la productividad de las v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Though it has been shown that the effects sought with deficit irrigation are attenuated by very high temperatures ( Torres et al, 2018a ), in Chile most of the vineyard areas are subjected to seasonal water deficits (during spring and summer), especially in vineyards in the north of the country where a semi-arid climate is dominant ( Bavestrello-Riquelme et al, 2012 ). Although protocols have been established for the optimization of water use in these areas, such as water reuse or regulated deficit irrigation, which allow the physiological stress of vines to overcome [ International Organisation of Vine and Wine [OIV], 2016 ], the low levels of water available and the long periods of drought cause extreme water stress in grapevines.…”
Section: Main Problems In Chilean Grapevinesmentioning
confidence: 99%
“…Though it has been shown that the effects sought with deficit irrigation are attenuated by very high temperatures ( Torres et al, 2018a ), in Chile most of the vineyard areas are subjected to seasonal water deficits (during spring and summer), especially in vineyards in the north of the country where a semi-arid climate is dominant ( Bavestrello-Riquelme et al, 2012 ). Although protocols have been established for the optimization of water use in these areas, such as water reuse or regulated deficit irrigation, which allow the physiological stress of vines to overcome [ International Organisation of Vine and Wine [OIV], 2016 ], the low levels of water available and the long periods of drought cause extreme water stress in grapevines.…”
Section: Main Problems In Chilean Grapevinesmentioning
confidence: 99%
“…Moscatel Amarilla (synonyms: Torrontés and Torrontés Riojano) and cv. Moscatel Negra (synonym: Canela) ( Figure 2) were grafted onto three commercial rootstocks (1103 Paulsen, 140 Ruggeri and Harmony) and one naturalized genotype (R32) selected in Northern Chile due to their tolerance to water deficit [19,25,26]. The vineyard was established in the winter of 2016 in a replanting soil previously planted with Vitis vinifera grapevines.…”
Section: Characterization Of Study Site Plant Materials and Experimenmentioning
confidence: 99%
“…Osmotic adjustment, as a tolerance mechanism, has been reported to relate to the active accumulation of solutes such as soluble sugars, organic acids and proline (Castellarin et al, 2007;Szabados & Savouré 2010). This allows cellular turgor to be maintained at low water potentials and at the same time favours physiological processes such as cell growth, stomatal opening and photosynthesis (Bavestrello-Riquelme et al, 2013).…”
Section: /8mentioning
confidence: 99%